Empire and catastrophe : decolonization and environmental disaster in North Africa and Mediterranean France since 1954 - Segalla, Spencer D. (France overseas., 2020)
"Empire and Catastrophe examines natural and anthropogenic disasters during the years of decolonization in Algeria, Morocco, and France, and explores how environmental catastrophes impacted the dissolution of France's empire in North Africa"--